Peculiarities of the activity of the class leader in the pedagogical psychological study of students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is one of the topical issues of today, and the scientific theoretical literature devoted to the study of the specific features of the activity of the class leader in the pedagogicalpsychological study of students is analyzed.